Narrativas de dos personas con discapacidad física sobre su experiencia y ajuste psicológico a través de la práctica del deporte adaptado - Hincapié Jiménez, Paula Catalina; Moreno Saavedra, Melanie Dayanna (Universidad Antonio Nariño, 2021)
This research analyzes the narratives of a group of people with physical disabilities about their experience and psychological adjustment through the practice of adapted sport. The methodology used is qualitative, with a hermeneutical historical approach, with a descriptive exploratory scope in the study. The participants were two people with acquired physical disabilities, from Bogotá, Colombia. The technique chosen to collect the information was the open interview and inductive categorization was used for its analysis. The results allowed us to explore the experiences and beliefs they had about sports practice before having a physical disability, the experiences and psychological adjustments that they elaborated through the practice of adapted sports. Among the most significant findings, the lack of knowledge of the adapted sport by the participants before becoming disabled stands out, in addition to the fact that the practice of sport is a crucial factor in the rehabilitation process, psychological adjustment, and in the improvement of quality of life. The participants perceive a lack of support from various institutions, especially the Colombian government, a backwardness in the infrastructure of Colombian cities, resulting in the adjustment to disability being a prolonged and difficult process that does not end, but it does go away. evolving.